Norms of Arousal and Valence for 908 Portuguese Words - Oliveira, Nelson Rocha de (2013)
Norms of arousal and valence for 908 Portuguese words were collected using SAM (Self-Assessment Manikin). In this study 4359 undergraduates from four universities participated. Words from each of the affective space quadrant were identified suggesting that they can be categorized along the arousal (from relaxing to more arousing words) and valence (from unpleasant to pleasant words) emotional dimensions. The reliability of the norms for valence (r = 0,97) and arousal (r = 0,94) was high and significant. Results showed that arousal and valence were not associated with sex, age or printed word frequency indicating that the factors can be considered orthogonal.